Europeesche Lagere School and the Birth of Bumiputera Intellectual Elite in Bojonegoro, East Java - Pratiwi, Evita; Husain, Sarkawi B (Paramita: Historical Studies Journal, 2021)
This article discusses the implementation of schools for European children to the birth of the Bumiputera elite in Bojonegoro in 1892-1942. The ethical politics that were introduced in the early 20th century had a significant influence on the development of colonial education in Bojonegoro. In addition, the awareness of the colonial education presence for European children during the Dutch colonial rule also influenced the presence of European elementary schools in this city. It was purposed to facilitate the majority of European children whose parents were colonial employees, plantation owners, or the gas industry. This article is the result of research using historical methods, namely, source collection, source verification or criticism, analysis, and writing or historiography. The first European Elementary School (Europeesche Lagere School) opened in Bojonegoro in 1892 which was located in the Bojonegoro District. This school applied the same rules as schools in the Netherlands. Initially the school only accepted students of European nationality, but in later development it also accepted Bumiputera children with strict conditions. The school, which was intended to produce European educated people, then also gave birth to a new intellectual elite called as Bumiputera, who later became the driving force for movement and press organizations.Artikel ini membahas tentang penyelenggaraan sekolah untuk anak-anak Eropa hingga lahirnya elit bumiputera yang ada di Bojonegoro pada tahun 1892-1942. Politik etis yang digulirkan pada awal abad ke-20 memberi pengaruh yang signifikan terhadap berkembangnya pendidikan kolonial di Bojonegoro. Selain itu, kesadaran untuk hadirnya pendidikan kolonial untuk anak-anak Eropa pada masa pemerintahan kolonial Belanda turut berpengaruh pada hadirnya sekolah dasar Eropa di kota ini. Hal ini untuk memfasilitasi banyakanya anak-anak Eropa yang orang tuanya menjadi pegawai kolonial, pemilik perkebunan, atau industri gas. Artikel ini merupakan hasil penelitian dengan menggunakan metode sejarah yaitu, pengumpulan sumber, verifikasi atau kritik sumber, analisis,  dan penulisan atau historiografi. Sekolah Dasar Eropa (Europeesche Lagere School)  pertama yang dibuka di Bojonegoro yakni pada tahun 1892 yang berlokasi di Distrik Bojonegoro. Sekolah ini menerapkan peraturan yang sama dengan sekolah yang ada di Belanda. Awalnya sekolah hanya menerima murid-murid berkebangsaan Eropa, namun dalam perkembangan kemudian juga menerima anak-anak bumiputera dengan persyaratan yang ketat. Sekolah yang diperuntukkan untuk mencetak kaum terdidik Eropa, kemudian   juga melahirkan elit intelektual baru bumiputera yang kemudian menjadi penggerak organisasi pergerakan dan pers.